Managing projects : create your schedule, monitor your budget, meet your goals. (Boston, Massachusetts : Harvard Business Review Press, 2014)
Succinctly delivers information on managing projects, including drawing up a realistic schedule and project plan, monitoring key tasks and benchmarks, and communicating with stakeholders.
Includes index.
Includes bibliographical references and index.
Keywords: Project management; Project management